IMPROVING STUDENTS' LEARNING OUTCOMES ON ASMAUL HUSNA MATERIAL THROUGH THE DISCOVERY LEARNING METHOD AT SMP NEGERI 2 WOYLA - Dewi, Fitri; Kasmawati (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Asma Ul-Husna is a good name of God for Muslims. By memorizing Asma Ul-Husna, a person can be expected to increase his/her faith and piety to God. Many students find it difficult to understand Asma Ul-Husna, this is certainly a problem that needs to be solved, to find out what problems are faced in Islamic Religious Education lessons, especially in the material of Asma Ul-Husna, it is necessary to conduct classroom action research. The purpose of this study was to determine the increase in student learning outcomes and the success of the Discovery Learning method in improving student learning achievement in the material of Asma Ul-Husna. This study uses action research, namely action research to solve learning problems in the classroom and is included in descriptive research. The results of the study showed that the Discovery Learning method can improve student learning outcomes, especially in the material of Asma Ul-Husna.